Soil seed bank dynamics in response to an extreme flood event in a riparian habitat. Issue 6 (13th September 2014) - Osunkoya, Olusegun O.; Ali, Sadiq; Nguyen, Thi; Perrett, Christine; Shabbir, Asad; Navie, Sheldon; Belgeri, Amalia; Dhileepan, K.; Adkins, Steve
Abstract: A significantly increased water regime can lead to inundation of rivers, creeks and surrounding floodplains‐ and thus impact on the temporal dynamics of both the extant vegetation and the dormant, but viable soil‐seed bank of riparian corridors. The study documented changes in the soil seed‐bank along riparian corridors before and after a major flood event in January 2011 in southeast Queensland, Australia. The study site was a major river (the Mooleyember creek) near Roma, Central Queensland impacted by the extreme flood event and where baseline ecological data on riparian seed‐bank populations have previously been collected in 2007, 2008 and 2009. After the major flood event, we collected further soil samples from the same locations in spring/summer (November–December 2011) and in early autumn (March 2012). Thereafter, the soils were exposed to adequate warmth and moisture under glasshouse conditions, and emerged seedlings identified taxonomically. Flooding increased seed‐bank abundance but decreased its species richness and diversity. However, flood impact was less than that of yearly effect but greater than that of seasonal variation. Seeds of trees and shrubs were few in the soil, and were negatively affected by the flood; those of herbaceous and graminoids were numerous and proliferate after the flood. Seed‐banks of weedy and/or exotic species were no more affected by the flood than those of native and/or non‐invasive species. Overall, the studied riparian zone showed evidence of a quick recovery of its seed‐bank over time, and can be considered to be resilient to an extreme flood event.